Fluctuating Open Heavy Flavour Energy Loss in a Strongly Coupled Plasma with Observables from RHIC and the LHC - Ngwenya, Blessed Arthur (Department of Physics, 2021)
We present predictions for the suppression (using the nuclear modification factor) of B-mesons using AdS/CFT techniques assuming a strongly coupled quark-gluon plasma (QGP). These energy loss predictions are presented for collision energies √ sNN = 2.76 TeV for central collisions and √ sNN = 5.5 TeV for various centrality classes. There are some uncertainties in terms of how we phenomenologicaly apply energy loss calculations computed in AdS/CFT. One uncertainty is related to how the diffusion coefficient behaves as a function of momentum in AdS/CFT. We make predictions for the two known limits, one where the diffusion coefficient depends on momentum and one where the diffusion coefficient is momentum independent. There also exists systematic theoretical uncertainties associated with the mapping of parameters in N = 4 SYM theory to QCD. We look at two reasonable sets of parameters to try and capture these uncertainties. We will also present results of the v2(pT ) for B-mesons describing the azimuthal anisotropy at √ sNN = 2.76 TeV for central collisions and √ sNN = 5.5 TeV for central, semi-central and peripheral collisions.